TEACHER’S SPECIAL KNOWLEDGE AND THEIR ROLE IN CHILDREN’S PHYSICAL EDUCAT - Azizov Muhammad Azamovich (Galaxy International Interdisciplinary Research Journal, 2023)
The publication reveals the meaning and methods of formation of special knowledge in the process of preparing teachers for work on physical education of children of preschool and primary school age. According to the results of a survey conducted among teachers of higher educational institutions of Ukraine, special knowledge is divided by importance. The results of the survey showed that the knowledge about the means, methods and forms of physical education of children, which are the basis of the physical education system, is of decisive importance in the physical education of children of the specified age.